2003
DOI: 10.1076/orbi.22.4.235.17248
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of benign eyelid skin lesions in the minor operation theatre

Abstract: Histopathologic confirmation may be necessary for most cases in the MOT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
8
0
7
Order By: Relevance
“…(9) Furthermore, accuracy was found to increase with greater professional experience, as was the case in the present study. (2,8,11) The accuracy of participants in determining the histological type of tumours was lower than in determining the presence of a malignancy, as shown in Tables 1 and 2. Of all malignant eyelid tumours, diagnostic accuracy was highest for BCC at 89%.…”
Section: Accuracy In Diagnosing Malignant Lesions Versus Experience Amentioning
confidence: 99%
See 4 more Smart Citations
“…(9) Furthermore, accuracy was found to increase with greater professional experience, as was the case in the present study. (2,8,11) The accuracy of participants in determining the histological type of tumours was lower than in determining the presence of a malignancy, as shown in Tables 1 and 2. Of all malignant eyelid tumours, diagnostic accuracy was highest for BCC at 89%.…”
Section: Accuracy In Diagnosing Malignant Lesions Versus Experience Amentioning
confidence: 99%
“…For example, Kersten et al found a high sensitivity in the clinical diagnosis of malignant lesions based on the experience of one very highly skilled professional. (8) This increases the internal validity of the study, but decreases its external validity because its results are less reproducible.…”
Section: Accuracy In Diagnosing Malignant Lesions Versus Experience Amentioning
confidence: 99%
See 3 more Smart Citations